Ebola virus entry requires the host-programmed recognition of an intracellular receptor - Miller, Emily Happy; Obernosterer, Gregor; Raaben, Matthijs; Herbert, Andrew S; Deffieu, Maika S; Krishnan, Anuja; Ndungo, Esther; Sandesara, Rohini G; Carette, Jan E; Kuehne, Ana I; Ruthel, Gordon; Pfeffer, Suzanne R; et al. (The EMBO journal, 2012)
Ebola and Marburg filoviruses cause deadly outbreaks of haemorrhagic fever. Despite considerable efforts, no essential cellular receptors for filovirus entry have been identified. We showed previously that Niemann‐Pick C1 (NPC1), a lysosomal cholesterol transporter, is required for filovirus entry. Here, we demonstrate that NPC1 is a critical filovirus receptor. Human NPC1 fulfills a cardinal property of viral receptors: it confers susceptibility to filovirus infection when expressed in non‐permissive reptilian cells. The second luminal domain of NPC1 binds directly and specifically to the viral glycoprotein, GP, and a synthetic single‐pass membrane protein containing this domain has viral receptor activity. Purified NPC1 binds only to a cleaved form of GP that is generated within cells during entry, and only viruses containing cleaved GP can utilize a receptor retargeted to the cell surface. Our findings support a model in which GP cleavage by endosomal cysteine proteases unmasks the binding site for NPC1, and GP–NPC1 engagement within lysosomes promotes a late step in entry proximal to viral escape into the host cytoplasm. NPC1 is the first known viral receptor that recognizes its ligand within an intracellular compartment and not at the plasma membrane. Niemann‐Pick C1 (NPC1), a lysosomal cholesterol transporter, is known to be required for Ebola virus entry. Here, NPC1 is shown to be sufficient for Ebola infection by directly binding the viral glycoprotein, GP, after its NPC1‐binding site is unmasked by endosomal protease cleavage.